Factor Price Equalization in a Dynamic Economy - Stiglitz, Joseph E. (Journal of Political Economy, 1970)
The purpose of this paper is to investigate in detail the long-run supply responses of capital and their implications for the classical propositions. We focus on the behavior of a two-country model in which the long-run rate of interest in each country is fixed, for example, by the pure rate of time preference in the case of "rational" savings behavior, or by the savings behavior of capitalists if workers save nothing. After setting up the basic model in Section I, and analyzing the pre-trade equilibrium in Section II, we investigate the long-run free-trade equilibrium in Section III. In Section IV, we show that, because the high interest rate (high time preference) country is willing to trade future consumption for present consumption with the low interest rate country, it always has a lower long-run consumption with free trade than pre-trade, and conversely for the low interest rate economy. In Section V, the patterns of specialization are investigated. Section VI considers the effects of trade policy on the long-run equilibrium; it is shown that a tariff (export subsidy) may lead to a higher consumption per capita in both countries. Section VII considers some extensions of the analysis. In the Appendix, the nature of the dynamic path is analyzed.